Recursos de tecnologia assistiva para avaliação de hipóteses de escrita de alunos com paralisia cerebral - Moralles, Adriana (2021)
The present work focuses on investigating the writing hypotheses of students with Cerebral Palsy who are in the process of literacy, seeking solutions through assistive technology (TA) resources. The objectives were to evaluate the performance of students with Cerebral Palsy in relation to writing hypotheses, using assistive technology resources such as the mobile alphabet and computer access for alternative writing, and to characterize the challenges and strategies implemented for the literacy process of these students. This is a multiple case study that had as direct participants three students with cerebral palsy in literacy process, respectively at eight and nine years of age, enrolled in elementary school I of the Municipal and State networks of a city in the interior of São Paulo, which receive specialized educational care (ESA) in a convened institution. As indirect participants, the teachers who accompany these students in the ESA, in the common room and their guardians (mothers and grandmothers). Instruments applied to characterize the students, were: GMFCS) - Extended and Revised Gross Motor Function Classification System; (MACS) - Manual Skill Classification System and (CFCS) - Communication Function Classification System for individuals with CP, a protocol for assessing accessibility to the computer for students with PC; Semi-structured interviews with teachers from the common room, the ESA and with the guardians; and an event recording protocol constructed by the researcher, in addition to a field diary. The procedures include the analysis of the students' needs for the implementation of alternative writing resources based on the demands of each of the participants in the ESA and the analysis of the writing hypothesis of these students in evaluation sessions that ranged from one to two individual meetings, with proposals for recognition and naming of letters, and written using mobile alphabet and conventional keyboard. All sessions were filmed and analyzed to characterize the students' performance regarding writing, in the literacy process, as well as the need to adapt resources for the implementation of alternative writing in computer. The interviews with the teachers and guardians were recorded in audio and analyzed through content analysis. In all three cases, the teachers and family members indicated the challenges in the proposition of specific activities for literacy in view of the motor and communicative commitment of the students, with the motivation and interest of the students as strengths in the process. In the direct evaluation with the participants, it was possible to identify the hypothesis of writing of two with the use of the mobile alphabet, one at the pre-silabic level and the other in the silabic-alphabetic. With the third participant, the survey conducted in only one session was not enough to achieve a robust result in this item. It was also identified that the three participants are potential candidates for the use of the computer for alternative writing purposes, with adaptations related to the typing functions of the operating system itself, in addition to the use of acrylic hives to facilitate typing. Suggestions about other types of TA features are presented. It is considered that the study can raise relevant points for the area of Special Education when it comes to the schooling process of students with cerebral palsy and the needs of differentiated processes and resources for the quality of the proposed pedagogical work.